Determinants of adoption of sustainable agricultural practices among maize producers in Northern Uganda - Dick Chune Midamba; Mary Kwesiga; Kevin Okoth Ouko (Cogent Social Sciences, 2024)
Sustainable agricultural practices (SAPs) increase crop productivity. This is achieved by increasing soil fertility, preserving moisture in the soil, and reducing pest and disease build-up, among other significant roles. Strikingly, maize farmers are still deeply rooted into the traditional methods of production which do not consider the adoption of SAPs. As such, they report low maize yields. Similarly, despite government efforts to increase the adoption rate, farmers remain reluctant to adopt SAPs. Therefore, this study aims to determine the adoption intensity of SAPs and its determinants using data collected from 101 randomly selected farmers in Northern Uganda. The adoption index (AI) and Tobit model approaches were used to determine the adoption intensity and its determinants, respectively. Based on the results, adoption intensity stood at 70%, while the determinants of adoption of the selected SAPs were education level (P < 0.05), household size (P < 0.05), farm size (P < 0.01), ICT use (P < 0.05), access to market information (P < 0.01), extension visits (P < 0.05), and credit access (P < 0.10). The study recommended that smallholder farmers’ use of ICT in accessing information on the adoption of SAPs among other agricultural information, strengthening adult literacy programs, increasing extension visits, and encouraging farmers to access credit from low interest rates financial institutions would help in increasing the level of adoption of SAPs.